THE IMAGE OF A JUST RULER IN NAVOYI’S CREATION - Ikramov Amriddin Toyirovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article talks about the role of a just ruler, his duties and responsibilities in the works of Alisher Navoi. Also, the images of other rulers in "Khamsa" and their views on life are presented.